Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Is $dx/dy = 1/(dy/dx)$ in calculus? So confused about this matter....

Also, what would be the proof of it? eg theorem.

Edit: by chain rule, $\frac{dy}{dx}\frac{dx}{dy} = dy/dy =1$, so this confuses me...

share|improve this question
This is imprecise. What you are asking is: what is $(f^{-1})'$ in terms of $f'$? –  wj32 Feb 2 '13 at 4:39

2 Answers 2

up vote 12 down vote accepted

The precise statement is as follows.

Let $ I $ be an open interval, and suppose that $ f: I \to \mathbb{R} $ is one-to-one and continuous on $ I $. If $ f $ is differentiable at $ a \in I $ and $ f'(a) \neq 0 $, then $ f^{-1}: f[I] \to I $ is differentiable at $ b = f(a) $ and $$ (f^{-1})'(b) = \frac{1}{f'(a)}. $$

Using Leibniz’s notation, the formula above can be expressed as $$ \frac{dx}{dy} \Bigg|_{y = b} = \frac{1}{\left( \dfrac{dy}{dx} \Bigg|_{x = a} \right)}. $$

share|improve this answer
An important point is evaluating the derivatives at the correct points as shown here. –  Ross Millikan Feb 2 '13 at 4:48

If the real variables $x$ and $y$ are dependent functionally on each other, say by the equations $y = f(x)$ and $x = g(y)$, then where things are differentiable, we do indeed have an equation

$$ \frac{dy}{dx} = \frac{1}{\frac{dx}{dy}} $$

and the most straightforward proof is as you indicated by the chain rule:

$$ \frac{dy}{dx} \frac{dx}{dy} = \frac{dy}{dy} = 1$$

and then solving the equation

$$ \frac{dy}{dx} \frac{dx}{dy} = 1$$

for $\frac{dy}{dx}$.

The argument can be rephrased in terms of functions rather than dependent variables: from the identity

$$ x = g(f(x)) $$

we differentiate to obtain

$$ 1 = g'(f(x)) f'(x) $$

and thus the analogous identity

$$ f'(x) = \frac{1}{g'(f(x))} $$

More generally, in the language of differential forms, the expression $\frac{dy}{dx}$ is defined to be the expression satisfying

$$ dy = \frac{dy}{dx} dx $$

if that is possible. When both $\frac{dy}{dx}$ and $\frac{dx}{dy}$ are defined, then we have two equations

$$ dy = \frac{dy}{dx} dx \qquad \qquad dx = \frac{dx}{dy} dy $$

and can substitute to obtain

$$ dy = \frac{dy}{dx} \frac{dx}{dy} dy $$

and so we again have

$$\frac{dy}{dx} = \frac{1}{\frac{dx}{dy}} $$

wherever $dy$ is nonvanishing. An example of a situation where both are defined is if the variables $x$ and $y$ are functionally related by a differentiable equation $f(x,y) = 0$. Taking the differential gives

$$ f_1(x,y) dx + f_2(x,y) dy = 0$$

where $f_1$ is the derivative of the two-variable function $f$ with respect to the first variable. When both $f_1$ and $f_2$ are nonzero, we can solve the equation in both ways to see that both $\frac{dx}{dy}$ and $\frac{dy}{dx}$ are defined.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.